2023
DOI: 10.1038/s41598-023-38094-w
|View full text |Cite
|
Sign up to set email alerts
|

Sunflower seed cake as a source of nutrients in gluten-free bread

Abstract: An increase in the demand for cold-pressed vegetable oils can be observed, e.g. from sunflower. The press cake formed during sunflower oil production can also be an important source of protein, carbohydrates, and phenolic compounds. The aim of the study was to examine the quality of gluten-free breads fortified with sunflower seed cake. The fortified products were characterized by lower moisture content (49.35–48.87%). The bake loss parameter decreased after the use of the highest 15% dose of the sunflower cak… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
4
0
3

Year Published

2024
2024
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(8 citation statements)
references
References 43 publications
1
4
0
3
Order By: Relevance
“…The control wheat bread had higher volume and specific volume compared with composite bread loaves. (18.24 N and 32.15 mj respectively) compared to their control (10.33N and 14.25 mj respectively) Looking closely at the our result differences with Naderi and Zarringhalami [81] who found that the qualitative characteristics of bread samples that addition of sesame flour to bread formulation tends to decrease crumb hardness, also differences line with Blicharz-Kania et al [82] who studied sun flower cake addition resulted exhibited lower hardness and chewiness.…”
Section: Physical Properties Of Selected Pan Breadsupporting
confidence: 90%
“…The control wheat bread had higher volume and specific volume compared with composite bread loaves. (18.24 N and 32.15 mj respectively) compared to their control (10.33N and 14.25 mj respectively) Looking closely at the our result differences with Naderi and Zarringhalami [81] who found that the qualitative characteristics of bread samples that addition of sesame flour to bread formulation tends to decrease crumb hardness, also differences line with Blicharz-Kania et al [82] who studied sun flower cake addition resulted exhibited lower hardness and chewiness.…”
Section: Physical Properties Of Selected Pan Breadsupporting
confidence: 90%
“…При переработке подсолнечника на масло образуются твердые отходы -жмыхи и шроты. Жмыхи, получаемые при извлечении масла прессовым способом, составляют до 75% от массы сырья; шроты, получаемые при извлечении масла экстракционным способом, составляют до 60% от массы сырья [1,2]. Жмыхи и шроты используются преимущественно в кормовых целях, но в последние годы во многих странах Европы разрабатываются технологии их переработки в пищевые ингредиенты.…”
Section: Introductionunclassified
“…Подсолнечный белок вызывает интерес как перспективный ингредиент пищевых продуктов. В форме изолятов и концентратов он может применяться для обогащения белком мучных изделий, например в смеси с пшеничной мукой [1,6]. Такие ингредиенты наиболее востребованы при производстве безглютеновых изделий, так как их состав является менее полноценным в сравнении с традиционным.…”
Section: Introductionunclassified
See 1 more Smart Citation
“…Source: Author's analysis on the basis of:[21][22][23][27][28][29][30][31][32][33][34][35][36][37][38][39][40].…”
mentioning
confidence: 99%